Return Migrants Reintegration Projects in West Africa: Critical Notes on the Sahel - Eyebiyi, Elieth; Allossoukpo, Eugène (The Journal of US Africa -Studies, 2021)
Migration issue is more than ever on the agenda of global concerns, particularly with regard to Africa, even though human mobility remains essentially internal on the African continent and rooted in centuries-old circulatory traditions. While a large literature emphasizes the criminalization of migration from the South to the North, but also the policies of outsourcing borders and the control of flows, the links between migration and development are still poorly studied, particularly with regard to the returnees, expelled and other categories (re) integration. However, return migrants are often at the heart of different logics and realities in tension, especially in the context of various reintegration projects, with mixed results. This paper contributes to rethink critically the public policies of reintegration of return migrants in Sub-Saharan Africa as a component of the European Union governance of migration, and in a context of regional free movement promotion. It is based on a combined analysis of some projects implemented as part of the transfer of European migration governance policies and measuring the scope, but also their inconsistencies. Key words: Return migrants; Migration policy; Reintegration projects; Sahel; West Africa